2013
DOI: 10.3724/sp.j.1037.2013.00045
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF Cr PLATING LAYER ON SHEAR STRENGTH AND INTERFACE BONDING CHARACTERISTICS OF MILD STEEL/CFRP JOINT BY LASER HEATING

Abstract: The carbon fiber reinforced polymer (CFRP) has been widely used in aerospace and military fields, whereas it is still at its initial stage in the field of automobile manufacturing, wind power generation and so on. One of the main reasons to restrict its wide application is that the strength of metal/CFRP joint is very low and cannot meet the industrial requirements. In this study, an investigation of the laser joining between CFRP and mild steel with Cr electroplating was presented. The influence of Cr plating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 8 publications
0
15
0
1
Order By: Relevance
“…However, the formation mechanism of porosities in CFRP during laser joining of the CFRP and metal is still unclear. Shan et al [25,29] found that when the temperature is higher than 350°C, the resin matrix of CFRP pyrolysis occurs, producing gaseous products such as CO 2 and NH 3 . The hydrocarbon series gases are detected by a Q-mass spectrometer during the laser joining of SUS304 stainless steel and PET [33].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the formation mechanism of porosities in CFRP during laser joining of the CFRP and metal is still unclear. Shan et al [25,29] found that when the temperature is higher than 350°C, the resin matrix of CFRP pyrolysis occurs, producing gaseous products such as CO 2 and NH 3 . The hydrocarbon series gases are detected by a Q-mass spectrometer during the laser joining of SUS304 stainless steel and PET [33].…”
Section: Introductionmentioning
confidence: 99%
“…One significant issue related to the laser joining of polymers and CFRP to metal is the porosity formation in the joining area caused by laser heating [25,[29][30][31][32][33][34][35]. When laser joining magnesium alloy and amorphous polyethylene terephthalate (PET), many small porosities are formed in the interior of the PET resin matrix near the interface [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is inferred that the new generated Al-O-C is contained in the Tan et al 27 studied effects of Cr plating layer on shear strength and interface bonding characteristics of mild steel/glass fiber reinforced polymers (GFRP) joint by laser heating. They also found that the metal Cr facilitated the opening of C5O groups in polymers resulting in the generation of Cr-O-C compounds.…”
Section: X-ray Photoelectron Spectroscopy (Xps)mentioning
confidence: 99%
“…Katayama and Kawahito [22] exhibited that the laser irradiated on stainless steel could generate a Cr 2 O 3 transition layer on the interface of plastic/stainless steel. Moreover, the research of Tan et al [23] revealed that the existence of the Cr layer on the steel surface enhanced the shear strength of the CFRP/steel joint by the Cr-O-PA6T bonding along the joint interface. e Roesner et al [24] demonstrated that the machined microgrooves on the metal surface increased the strength of the laser joined plastic/aluminum joint to 24 MPa.…”
Section: Introductionmentioning
confidence: 99%